How to increase rural NEETs professional involvement in agriculture? The role of vocational training packages improvement - Simões, F. (Green economy: Challenges and opportunities for rural NEETs, 2020)
The aim of this presentation is to explore how training experiences in agriculture can be tailored to improve the prospects of low-qualified, rural youths who are neither in employment, nor in education or training (NEET) being involved in the sector. Based on two qualitative sequential studies, we found that: (a) low-qualified rural NEETs depict negative perceptions about agriculture; these negative perceptions are similar, in content, to those reported in other studies by youths originating in (sub)urban areas; and (b) a strong participatory stand to design and run training for agriculture has the potential to tailor packages that improve outreaching these youths. This approach can prevent rural NEETs negative representations about the sector and may tackle the mismatch between training offer and local economy opportunities.